2001
DOI: 10.1002/ps.401
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and translaminar bioavailability of two neonicotinoid insecticides after foliar application to cabbage and cotton

Abstract: A laboratory study was undertaken to investigate the leaf systemic properties and the translaminar aphicidal activity of two commercialised neonicotinoid (chloronicotinyl) insecticides. For that purpose [14C]imidacloprid was subjected to uptake and translocation studies in cabbage and cotton after foliar application. Foliar penetration and short-term translocation patterns of imidacloprid were similar in both plant species. Nevertheless imidacloprid penetrated twice as much into cabbage leaves as it did into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
15

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 21 publications
3
37
1
15
Order By: Relevance
“…The low octanol/water partition coefficient furthermore indicates low adsorption behaviour of the active ingredient into organic matter. Nauen et al [17] and Buchholz and Nauen [33] reported that imidacloprid can be penetrated through plant cuticles via diffusion, but in contrary to our experiments, the active ingredient was applied using surfactants or emulsifiers (leaf wetting agents) favouring penetration. However, the main portion of imidacloprid applied to the plants resided on the surface or in the epicuticular waxes of the cuticle.…”
Section: Foliar Spray Applicationcontrasting
confidence: 68%
See 1 more Smart Citation
“…The low octanol/water partition coefficient furthermore indicates low adsorption behaviour of the active ingredient into organic matter. Nauen et al [17] and Buchholz and Nauen [33] reported that imidacloprid can be penetrated through plant cuticles via diffusion, but in contrary to our experiments, the active ingredient was applied using surfactants or emulsifiers (leaf wetting agents) favouring penetration. However, the main portion of imidacloprid applied to the plants resided on the surface or in the epicuticular waxes of the cuticle.…”
Section: Foliar Spray Applicationcontrasting
confidence: 68%
“…It would minimize worker and consumer exposure to the pesticide, result in a uniform application, and prevent runoff of pesticide by spray drift into the environment. A comparative field study of the systemic efficacy of imidacloprid against whiteflies conducted by Buchholz and Nauen [33] revealed that the active ingredient was more effective after soil application as compared with foliar application. van Iersel et al [36] reported that the control of whiteflies was better after subirrigation than on hand-watered plants that received a drench application of imidacloprid.…”
Section: Root Uptake and Translocation After Chemigationmentioning
confidence: 99%
“…Neonicotinoids are mainly acropetally transported in the xylem [15], [16], [33]. Given clothianidin's prolonged (>9 month) half-life from field dissipation in soil [34], it is unlikely that, in just three weeks, degradation of residues in the root zone can explain the lack of acute effects on bees foraging on clover that bloomed after mowing.…”
Section: Discussionmentioning
confidence: 99%
“…Clothianidin is the least water-soluble neonicotinoid used on turf [34]. Sorption of neonicotinoids to soil organic components reduces the amount that is translocated [33], [35]. Translocation is driven by transpiration and plant growth, processes likely to be greater for foliage than for floral tissues and nectar.…”
Section: Discussionmentioning
confidence: 99%
“…However, S. maltophilia mainly degrades AAP and only transforms a part of AAP to low toxic metabolite IM 2-1 at a low molar ratio. It had been reported that AAP was superior after foliar application, whereas IMI soil application demonstrated a much greater systemic activity (Palumbo et al 1999;Buchholz and Nauen 2001) although the metabolic mechanism in soil was not clear. Based on our results, the low efficacy of AAP in soil application can be attributed to the fact that AAP could be easily degraded and the partial degraded intermetabolitedemethylated IM 2-1 remained less bioactivity.…”
Section: Discussionmentioning
confidence: 99%